Pengaruh Motovasi dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Telkom Akses (PTTA) Medan - Cindy Antika; Ade Rahma Ayu (CIVITAS: Jurnal Studi Manajemen, 2022)
the purpose of this research is to know how much influence of motivation and work discipline to employee performance at PT. Telkom Access (PTTA) Medan. The sample of this research were 54 people consisting from regional employees of Sumatera in 2020, using saturated sampling (census) was a sampling technique when all members of the population were used as samples. Data analysis using multiple regression test, data processing using SPSS. The results showed that partial motivation and work discipline have positive and significant, simultaneous motivation and work discipline have positive and significant effect to employee performance. So in this case the performance of employees at PT. Telkom Access (PTTA) Medan can be improved through motivation and work discipline.